“The closed door?” The relationship of the Ciganos with the labour market from the perspective of the employment and training officers - Candeias, P.; Caetano, P.; Mendes, M. M.; Magano, O. (Social Work and Society, 2023)
The employability of the Portuguese Roma, or Ciganos, is one of the major challenges that arises in contemporary Portuguese society, being transversal to other European countries, since a part of this population lack the necessary school and professional qualifications for their integration in the labour market. Employment and professional training centres can operate as institutional mediators between the Ciganos and the labour market. However, there are few studies about these public services and this article aims to fill this gap in terms of knowledge on this thematic. This paper is based on the analysis of the results derived from an online survey applied to employment centre directors and officers, aimed at unravelling the motives that justify, in their perspective, the low employability of Ciganos. Despise the results highlighted the greater emphasis on explanations of individual order and lesser reference to factors that are structural or focused on the employers. The contact with Cigano culture appears to be associated with a decrease of the importance of explanations of individual order and a higher weight of the explanations of structural order.